Knowledge treatment compliance and prevalence of known risk factors among patients attending glaucoma clinics at Eye Hospital Colombo - Piyasena, D.A.K.N (My University, 2008)
Glaucoma is the second leading cause of preventable blindness in the world. Blindness caused by glaucoma is irreversible. To describe the socio demographic characteristics , assess the knowledge of glaucoma , treatment compliance and proportion with known risk factors among patients attending glaucoma clinics at Eye Hospital. A descriptive cross sectional study was carried out at glaucoma clinics in Eye Hospital Colombo during the period August - November 2008. Diagnosed glaucoma patients attending glaucoma clinics of Eye Hospital Colombo were selected for the study. An interviewer administered pre tested questionnaire and a data extraction form were used for data collection interviewers. Among the 431 glaucoma patients a majority were females 57.5 percent ( n 60 years were 40.2 percent ( n = 173), 63 percent ( n=272) had O/L education 51 percent ( n=251) had Rs.10000 monthly income. Among patients 84.8 percent (n=370) knew the name of the disease, while 38.7 percent ( n=167) named as glaucoma, 45.5 percent ( n=196) referred as eye pressure.